2020
DOI: 10.1292/jvms.20-0477
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of bovine leukemia virus in beef cattle presented for slaughter in Egypt

Abstract: Bovine leukemia virus (BLV) is the etiological agent of enzootic bovine leukosis, the most common neoplastic disease of cattle worldwide and a serious problem for the cattle industry. Previous studies have shown the molecular prevalence of BLV and the coexistence of BLV genotype-1 and-4 in Egyptian dairy cattle; however, the molecular characteristics of BLV in Egyptian beef cattle are unknown. Therefore, we collected blood samples of 168 beef cattle from slaughterhouses in three governorates in Egypt. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Thus, we compared two commercial qPCR master mixes, the TBIRD qPCR master mix and the GeneAce qPCR master mix, for the Dual-CoCoMo assay. The TBIRD qPCR master mix, which has high sensitivity, specificity, and cost-effectiveness, is usually used for the Single-CoCoMo assay [10,11,29,31,33,34,[41][42][43][44][45]. In addition, the TBIRD qPCR master mix has been used in several multiplex qPCR assays [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we compared two commercial qPCR master mixes, the TBIRD qPCR master mix and the GeneAce qPCR master mix, for the Dual-CoCoMo assay. The TBIRD qPCR master mix, which has high sensitivity, specificity, and cost-effectiveness, is usually used for the Single-CoCoMo assay [10,11,29,31,33,34,[41][42][43][44][45]. In addition, the TBIRD qPCR master mix has been used in several multiplex qPCR assays [46].…”
Section: Discussionmentioning
confidence: 99%
“…BLV is highly prevalent in most regions, except for some European countries and Oceania [2]. For example, the proportion of BLV-positive cattle ranges from 28.0 to 40.9% in Japan [3], 40.0 to 48.0% in Korea [4], 31.0 to 41.9% in China [5,6], 11.0 to 100% in Thailand [7], 4.8 to 9.7% in the Philippines [8], 21.5 to 28.0% in Egypt [9,10], 37.04% in Myanmar [11], more than 40.0% in the USA [12], and 88.4% of dairy herds in Canada [13]. BLV infects cattle worldwide and has a severe economic impact on the cattle industry [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several serological studies have detected BLV infections among dairy cattle in Egypt from different regions, such as Kafr El Sheikh, Alexandria, and Menofia, with infection rates of 15.83% [52], and 20.8% in cows in Kafr El Sheikh, Qalyubia, and Menofia [53]. Our recent investigation of the distribution of BLV provirus revealed a 25-28% BLV infection rate for healthy male beef cattle in three slaughterhouses located in the central and southern regions of Egypt [54] and 21.5% for dairy cattle in five provinces located in the northern, central, and southern regions of Egypt [55]. According to our earlier reports, phylogenetic analysis of the partial env-gp51 sequence of the isolated BLV strains showed that BLV genotypes 1 and 4 coexist in dairy and beef cattle in Egypt from the 12 globally detected genotypes [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent investigation of the distribution of BLV provirus revealed a 25-28% BLV infection rate for healthy male beef cattle in three slaughterhouses located in the central and southern regions of Egypt [54] and 21.5% for dairy cattle in five provinces located in the northern, central, and southern regions of Egypt [55]. According to our earlier reports, phylogenetic analysis of the partial env-gp51 sequence of the isolated BLV strains showed that BLV genotypes 1 and 4 coexist in dairy and beef cattle in Egypt from the 12 globally detected genotypes [54,55]. Estimation of BLV PVL among dairy cattle in five provinces in Egypt [55] demonstrated that the BLV PVL level varied among different regions of Egypt with PVL ranging from 7 to 98,725 copies/10 5 cells as calculated by the BLV-CoCoMo quantitative polymerase chain reaction (qPCR)-2 method for the quantitative measurement of PVL [17,56].…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the lack of readily available effective treatments and vaccines, BLV infections have spread worldwide (7,8). Currently, 40.9% of the dairy cows over 6 months of age and 28.7% of breeding cattle in Japan (9), 94.2% of dairy herds in the USA (10), 36.7% of the cattle and 78.3% of the herds in Canada (11), over 81.8% of the cattle and 99.1% of the herds in Taiwan (12), over 50% of the cattle and 86.8% of the herds in Korea (13), ∼31-41.9% of the cattle in China (14,15), 4.8-9.7% of the cattle in the Philippines (16), 21.5-28.0% of the cattle in Egypt (17,18), and 9.1-37.04 % of the cattle in Myanmar (19,20) are BLV positive.…”
Section: Introductionmentioning
confidence: 99%